Submerged paleoshoreline mapping using high-resolution Chirp sub-bottom data, Northern Channel Islands platform, California, USA. Issue 1 (January 2020) - Laws, Alexander W.; Maloney, Jillian M.; Klotsko, Shannon; Gusick, Amy E.; Braje, Todd J.; Ball, David
Abstract: High-resolution Chirp sub-bottom data were obtained offshore from the Northern Channel Islands (NCI), California, to image submerged paleoshorelines and assess local uplift rates. Although modern bathymetry is often used for modeling paleoshorelines, Chirp data image paleoshorelines buried beneath sediment that obscures their seafloor expression. The NCI were a unified landmass during the last glacial maximum (LGM; ~20 ka), when eustatic sea level was ~120 m lower than present. We identified seven paleoshorelines, ranging from ~28 to 104 m in depth, across this now-submerged LGM platform. Paleoshoreline depths were compared to local sea-level curves to estimate ages, which suggest that some were reoccupied over multiple sea-level cycles. Additionally, previous studies determined conflicting uplift rates for the NCI, ranging from 0.16 to 1.5 m/ka. Our results suggest that a rate on the lower end of this range better fits the observed submerged paleoshorelines. Using the uplift rate of ~0.16 m/ka, we estimate that paleoshorelines formed during Marine Oxygen Isotope Stage 3, the LGM, and the Younger Dryas stade are preserved on the NCI platform. These results help clarify uplift rates for the NCI and illustrate the importance of sub-bottom data for mapping submerged paleoshorelines.